PENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MENGGUNAKAN MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION SISWA KELAS IV - Has Ramadhan, Rohanda; Zulhendri; Fadhilaturrahmi; Marta, Rusdial; Fitra Surya, Yenni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the critical thinking skills of fourth-grade students at SD Muhammadiyah 002 Penyasawan through the implementation of the Realistic Mathematics Education (RME) learning model. The background of this research stems from the low level of students’ critical thinking skills in Mathematics, as indicated by their limited ability to provide simple explanations, analyze information, and draw conclusions. Learning activities that remained teacher-centered caused students to become passive and unaccustomed to solving contextual problems. This research employed Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of the stages of planning, implementation, observation, and reflection. The research subjects consisted of 24 students. Data were collected through observation, critical thinking tests, and documentation, while the data analysis was carried out using both qualitative and quantitative approaches. The RME model was implemented through contextual problem presentation, group discussions, horizontal and vertical mathematization processes, and joint conclusion-making. The results showed a significant improvement in students’ critical thinking skills following the application of the RME model. In Cycle I, students’ mastery level had not yet reached the targeted criteria, with an average achievement of 54.16%, and many students still experienced difficulties in analyzing problems. After improvements were made in Cycle II, students’ critical thinking skills increased to 87.5%, successfully meeting the classical mastery criteria. Furthermore, students’ learning activities also improved, as reflected in their increased participation in discussions, confidence in expressing ideas, and ability to solve problems independently. In conclusion, the Realistic Mathematics Education model is effective in enhancing the critical thinking skills of fourth-grade students, particularly in Mathematics learning based on contextual problem solving.